Pengembangan Konten Multimedia Tiga Dimensi Pengolahan Air Kolong Pasca-Penambangan Timah pada Perangkat Telepon Bergerak - Andriana, Dian; Nugraheni, Ekasari; Riswantini, Dianadewi; Khotimah, Purnomo Husnul (LIPI Press, 2012)
Exploitation of tin mining in Province of Bangka Belitung Islands leave traces in the form of pit mines with poor water quality if used for fish farming. Water treatment method under the passive treatment that has been conducted by Limnology researchers in LIPI show pools of water quality improvement. A multimedia content in the form of 3-dimensional animation is made to further disseminate information about the benefits of the use of passive treatment as a medium of learning that can be accessed easily by the fish farmer or local community uses the internet on mobile devices. This paper describes the methodology of development of this multimedia content on mobile devices and includes discussion and testing of accessibility to the public.